2019
DOI: 10.1111/ijcp.13458
|View full text |Cite
|
Sign up to set email alerts
|

Elevated triglycerides on admission positively correlate with the severity of hypertriglyceridaemic pancreatitis

Abstract: Background Hypertriglycaeridemia has been positively associated with the risk of acute pancreatitis, but whether increased triglyceride (TG) levels are related to the severity of pancreatitis remains unclear. The aim of this study was to assess the relationship between hyperlipidaemia and disease severity of hypertriglycaeridemic pancreatitis. Methods From 2016 to 2018, patients with hypertriglyceridaemic pancreatitis presented within 24 hours from symptom onset were retrospectively enrolled. The severity was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 28 publications
(62 reference statements)
0
4
0
Order By: Relevance
“…Similar second messenger release mechanisms are induced in alcohol-associated acute pancreatitis by fatty acid ethyl esters (FAEEs) [81], and by fatty acids released from FAEEs or lipolysis of triglycerides in hypertriglyceridaemia [82], to inhibit mitochondria and aerobic ATP production. In general, there is a direct correlation between the severity of toxin exposure and that of acute pancreatitis, as in the case of serum triglyceride levels and the severity of acute pancreatitis [39,43,83].…”
Section: Pathophysiologymentioning
confidence: 99%
“…Similar second messenger release mechanisms are induced in alcohol-associated acute pancreatitis by fatty acid ethyl esters (FAEEs) [81], and by fatty acids released from FAEEs or lipolysis of triglycerides in hypertriglyceridaemia [82], to inhibit mitochondria and aerobic ATP production. In general, there is a direct correlation between the severity of toxin exposure and that of acute pancreatitis, as in the case of serum triglyceride levels and the severity of acute pancreatitis [39,43,83].…”
Section: Pathophysiologymentioning
confidence: 99%
“…Acute pancreatitis (AP) is one of the most common gastrointestinal diseases leading to hospital admissions 1 . The important role of hypertriglyceridemia in AP is increasingly recognized 2 . It is generally believed that triglyceride (TG) levels more than 11.3 mmol/L (1000 mg/dL) is needed to trigger an episode of AP 3 .…”
Section: Introductionmentioning
confidence: 99%
“…Pancreatic necrosis, infected necrosis, organ failure, and persistent organ failure were all more frequent than patients without HTGP. Mortality and ICU length of stay was higher in HTGP patients [11]. A recent cohort study in China showed that with the increase of HTG, the mortality rate of patients and other clinical outcomes of organ failure and pancreatic necrosis increased significantly and gradually, which suggested that triglyceride levels were positively correlated with disease severity.…”
Section: Clinical Course and Natural Historymentioning
confidence: 94%